Evaluation of ziehl neelsen and light emitting diode fluorescent microscopy with reference to culture for the detection of mycobacterium tuberculosis complex from suspected tuberculosis patients. - Upadhyaya,Shambhu Kumar (2015)
ABSTRACT: The inadequate ability to rapidly and accurately diagnose active tuberculosis (TB) in developing countries including Nepal remains a major obstacle in global control of the disease. In Nepal, 45% of total population is infected with TB of which 60% are in the productive age group. Screening of TB patients and laboratory diagnosis of causative agent plays a significant role to control and eradicate TB. There is an urgent need for an appropriate TB diagnostic tool that is simple, rapid, sensitive and specific and can be made widely available so that 3 million missing TB cases and new cases as well as relapse cases can be detected. This study was performed in German Nepal Tuberculosis Project (GENETUP) laboratory with an objective to evaluate the diagnostic efficacy of two staining techniques (Ziehl-Neelsen and LED fluorochrome staining) for the detection of acid fast bacilli (AFB) in comparison to culture. A total of 325 samples were processed in this study in which 219 were from male and 106 were from female, among them, 56% of the samples were from the productive age group. From the total samples processed, 97 were AFB positive by ZN microscopy and 104 by LED fluorescent microscopy. Culture showed 121 positive results while 7 cultures were contaminated. Considering culture as gold standard for tuberculosis, sensitivity of ZN and LED fluorescent microscopy were found to be 70.8% and 72.5% and specificity were 94.9% and 92.4% respectively. From this study, it is concluded that LED fluorescent microscopy is potentially more suitable for laboratories to screen TB in resource-limited settings and countries like Nepal where the TB burden is comparatively high. From time and labor point of view, LED fluorescent microscopy was found to be very easier and faster than the conventional technique. So that, it is recommended that ZN microscope should be replaced by LED fluorescent microscope in the TB diagnostic centers. Key words: Acid fast bacilli, Light Emitting Diode fluorescent microscopy, Tuberculosis, Ziehl-Neelsen microscopy.